Dorsocaudal reconstruction of previous caudal septal resections with partial split spreader graft: Septal reconstruction with partial split spreader graft - Ekinci, Can; Can, Bilgen; Koçman, Atacan Emre (Journal of Surgery and Medicine, 2022)
Background/Aim: Nasal obstruction is caused mainly by nasal septal deviation, and submucosal resection is usually performed to treat this problem. However, if over-resected, nasal tip deprojection, deprojection of the dorsum, or pseudo-hump formation may be seen. Spreader grafts are used to restore the nasal septum in these cases, and different techniques have been described for this restoration; however, these techniques may not be the best fit for such restoration. This study presents a novel and effective method for septal reconstruction in patients with previous septal resections. Methods: Between March 2012 and October 2014, a case series of 14 male patients with tip deprojection and pseudo-hump formation who had undergone corrective surgery in our clinic was retrospectively examined. Partial-split, caudal extension costal spreader grafts were used and were fixed to the dorsum of the remnant septum cranially to prevent warping while avoiding nasal dorsum widening. Pre- and post-operative comparisons were performed, and the Nasal Obstructive Symptoms Evaluation questionnaire for the functional results and subjective Esthetic Appearance test for the esthetic outcomes were administered. Results: The mean age was 36.8 years (19–56 years), and the mean follow-up time was 14.6 months. Functional outcomes and esthetic appearance led to significantly improvements in all post-operative categories (P < 0.05) without any major complications. Common complaints were usually the same as seen in conventional rhinoplasty procedures, such as facial swelling, nasal stuffiness, pain, and/or epistaxis. None of the patients requested revision surgery. Conclusion: Using partial-split, caudal extension costal spreader grafts in the reconstruction of dorsocaudal septum in patients with previous septal resections appears to provide favorable functional and esthetic results.